2014
DOI: 10.22436/jmcs.010.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio Optimization Using Particle Swarm Optimization And Genetic Algorithm

Abstract: This study basically employs the Markowitz mean-variance model for portfolio selection problem. Since this model is classified as a quadratic programming model there is not any efficient algorithm to solve it. The goal of this study is to find a feasible portfolio with a minimum risk through the application of heuristic algorithm. The two PSO and GA algorithm has been used. The results show that PSO approach is suitable in portfolio optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Fourth, overseeing policy statements, capital market conditions and investment strategies to verify any changes. These steps are a continuous procedure in a portfolio (Kamali, 2014).…”
Section: Portfoliomentioning
confidence: 99%
“…Fourth, overseeing policy statements, capital market conditions and investment strategies to verify any changes. These steps are a continuous procedure in a portfolio (Kamali, 2014).…”
Section: Portfoliomentioning
confidence: 99%
“…PSO has been shown to be very competitive amongst other approaches to unconstrained portfolio optimization. Kamali showed that PSO was able to obtain higher quality portfolios in less time than a GA [88]. PSO, compared with a GA and an industry tool, proved to be a superior algorithm in nding solutions to portfolio optimization [194].…”
Section: Particle Swarm Optimizationmentioning
confidence: 99%
“…A variety of evolutionary and swarm intelligence algorithms have been proposed to solve the portfolio optimization problem. [5], [7], [15], [17], [46], [48], [75], [76], [79], [80], [88], [129], [166], [189],…”
Section: Representation Of Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since in the harmony, musician seek optimum solutions at each stage using the generated rules in the previous steps, and Because harmony search algorithm does not work well in the local optimum [19] and this action increases the execution time and reduce convergence of the algorithm [20], we use a genetic algorithm. Genetic algorithm increases the search space to achieve universal or near-universal response [21].For this purpose, we use two operators of genetic algorithm, crossover and mutation; In addition search Harmony operators in the stage production rules. So we implement the two operators on generated rules.…”
Section: Improvement Of the Proposed Algorithmmentioning
confidence: 99%